2019
DOI: 10.1038/s41598-018-36592-w
|View full text |Cite
|
Sign up to set email alerts
|

Globin E is a myoglobin-related, respiratory protein highly expressed in lungfish oocytes

Abstract: Globins are a classical model system for the studies of protein evolution and function. Recent studies have shown that – besides the well-known haemoglobin and myoglobin – additional globin-types occur in vertebrates that serve different functions. Globin E (GbE) was originally identified as an eye-specific protein of birds that is distantly related to myoglobin. GbE is also present in turtles and the coelacanth but appeared to have been lost in other vertebrates. Here, we show that GbE additionally occurs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…As none of the other globins (with the exception of GbE; see ) or, to the best of our knowledge, any other gene family show signs of gene amplification, it is unlikely that the multiplication of the Mb genes is caused by hypothetic whole‐genome amplifications putatively linked to the large lungfish genomes. Duplicated and even triplicated Mb genes have been known from some teleost species .…”
Section: Discussionmentioning
confidence: 92%
“…As none of the other globins (with the exception of GbE; see ) or, to the best of our knowledge, any other gene family show signs of gene amplification, it is unlikely that the multiplication of the Mb genes is caused by hypothetic whole‐genome amplifications putatively linked to the large lungfish genomes. Duplicated and even triplicated Mb genes have been known from some teleost species .…”
Section: Discussionmentioning
confidence: 92%
“…Cytoglobin is an intracellular respiratory globin ubiquitously expressed almost in all tissues. 66 It has been shown to prevent oxidative stress through scavenging excess ROS, 67 thereby maintaining physiological ROS levels. 68 Cytoglobin protected the cardiac progenitor cells against oxidative stress and promoted their survival.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroglobin (Ngb) emerged in early Metazoans around 800 million years ago from a common ancestor to Adgb and Globin X [ 69 , 77 ] and is found in vertebrates including ray-finned fishes, coelacanths, amphibians, lizards, turtles, birds, monotremes, marsupials and mammals, with the exception of lampreys, cartilaginous fishes and lungfishes [ 69 , 202 ] ( Fig. 2 ).…”
Section: Neuroglobinmentioning
confidence: 99%
“…More recently, a study showed that lungfish bear also multiple copies of GbE . Surprisingly, in contrast to avian location, the major sites of expression were ovaries and oocytes, whereas no detectable mRNA was found in the eye [ 202 ]. The physiological role of GbE in lungfish and more particularly in oocytes is still unclear, but it is conceivable that its main function might be to retrieve oxygen from water and support embryonic development.…”
Section: Globin Ementioning
confidence: 99%